Pengaruh Promosi, Harga, dan Citra Merek Terhadap Keputusan Pembelian pada Home Industri Keripik Cap Fajar - Dani Agus Tiningrum; Ustadus Sholihin; Iing Sri Hardiningrum (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to determine the effect of promotion, price, and brand image on consumer purchasing decisions in the Cap Fajar Chips Home Industry. The study uses a quantitative approach with a survey method. The study population is consumers who have made purchases at the store, with a total of 150 respondents selected as a sample. The data collection method is carried out through distributing questionnaires, then the data is analyzed using multiple linear regression techniques to test the effect of each independent variable, both partially and simultaneously, on purchasing decisions. The results of the analysis show that the promotion variable (X1) does not have a partial significant effect on purchasing decisions, as evidenced by a significance value of 0.502 (> 0.05). This indicates that the intensity or form of promotion carried out is not enough to directly influence consumer purchasing decisions. In contrast to promotions, the price variable (X2) is proven to have a positive and significant effect on purchasing decisions. A significance value of 0.000 (< 0.05) indicates that competitive and affordable pricing is an important factor that encourages consumers to choose Cap Fajar chips products. Similarly, the brand image variable (X3) has a partial significant influence on purchasing decisions, with a significance value of 0.013 (<0.05). This indicates that consumers' positive perceptions of brand reputation and quality can strengthen the desire to purchase. Simultaneously, the three variables—promotion, price, and brand image—have a significant influence on consumer purchasing decisions. This finding is evidenced by a significance value of 0.001 (<0.05). Based on the results of the study, it can be concluded that price and brand image are the dominant elements that determine purchasing decisions for Cap Fajar chips, while promotions require a more effective strategy to provide a real impact.